Strategic dimensions of institutional governance in corporate zakat mobilization: A TCT perspective on network efficiencies - Mohd Zaki, Adeeba Najihah; Bustaman, Hasnun Anip; Mat Rusok, Nur Hazelen; Mohd Nor, Nur Halida Haziaton; Ab Rahman, Siti Maziah (Journal of Islamic, Social, Economics and Development, 2026)
Within the contemporary Islamic economic paradigm, corporate zakat serves as a critical mechanism for wealth redistribution, capital purification, and the preservation of macroeconomic equilibrium. However, the operational capacity of this fiscal instrument remains constrained by suboptimal institutional alignment and structural compliance deficits. In the state of Kelantan, corporate contributions continuously plateau below 20% of the aggregate zakat revenue, exposing a profound gap between actual collections and fiscal potential. This conceptual paper addresses this structural deficit by constructing an integrated, multi-tiered framework of institutional governance for corporate zakat mobilization. Grounded in Transaction Cost Theory (TCT) and relational governance frameworks, we deconstruct corporate zakat governance into three distinct configurations: shared governance, lead governance, and network administrative organizations (NAOs). We posit that these structural mechanisms collectively mitigate behavioral uncertainties, minimize information asymmetries, and lower transaction monitoring costs for corporate payers (muzakki). Furthermore, the framework introduces corporate leadership quality as a vital conditional moderator that actively optimizes the path between these governance dimensions and institutional compliance. This paper contributes to the Islamic social finance literature by shifting the research paradigm from individual compliance intentions to firm-level transactional efficiencies.